1996
DOI: 10.1073/pnas.93.3.1259
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori attachment to gastric cells induces cytoskeletal rearrangements and tyrosine phosphorylation of host cell proteins.

Abstract: The consequences of Helicobacter pylori attachment to human gastric cells were examined by transmission electron microscopy and immunofluorescence microscopy. H. pylori attachment resulted in (i) effacement of microvilli at the site of attachment, (ii) cytoskeletal rearrangement directly beneath the bacterium, and (iii) cup/pedestal formation at the site of attachment. Doubleimmunofluorescence studies revealed that the cytoskeletal components actin, c-actinin, and talin are involved in the process. Immunoblot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
189
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(206 citation statements)
references
References 32 publications
8
189
2
7
Order By: Relevance
“…However, it must be noted that these investigators studied patients with dyspeptic symptoms without evidence of gastric or duodenal ulcer disease. Further studies revealed various modes of cell adhesion (3,(8)(9)(10)(11)(12) and according to some reports H. pylori was demonstrated in close proximity to parietal cells and even inside the canaliculi of resting (gastric) cells (4,8,10,13,14). …”
mentioning
confidence: 86%
See 2 more Smart Citations
“…However, it must be noted that these investigators studied patients with dyspeptic symptoms without evidence of gastric or duodenal ulcer disease. Further studies revealed various modes of cell adhesion (3,(8)(9)(10)(11)(12) and according to some reports H. pylori was demonstrated in close proximity to parietal cells and even inside the canaliculi of resting (gastric) cells (4,8,10,13,14). …”
mentioning
confidence: 86%
“…At the same time, however, Hazell et al (7) consistently observed penetration of the bacteria in the deep parts of the intercellular junctions. In contrast, many reports have demonstrated occasional (6,8,10,11,14,20,21) or frequent (12) internalisation of H. pylori in gastric mucous cells (8,10,11,14,20), parietal cells (4,14,20) or various cell lines (12,21,22). The intracellular organisms were mostly viable and sometimes associated with mucous droplets or granules (23) or vacuole spaces (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients that develop chronic gastritis following the initial infection are at greater risk of developing gastric ulcers and gastric cancer (reviewed in Suerbaum and Michetti, 2002). While H. pylori can be cultured on bacterial plates and in liquid culture, proliferation ceases once the bacteria are added to standard eukaryotic cell cultures and the bacteria round up and die (Kusters et al, 1997;Segal et al, 1996). Further, cancer cell lines most probably represent a late stage of the disease process, which may be the stage of least relevance when considering the effect of H. pylori on carcinogenesis.…”
Section: Gastric Organoids and Helicobacter Pylorimentioning
confidence: 99%
“…In one of the studies, many intracellular spiral H pylori were usually observed within defined membrane-bound vacuoles, but they did not appear to replicate and seemed to degenerate. 22 Other authors found that although many H pylori indeed degenerated, some of them maintained a normal ultrastructural morphology even after phagocytosis by immunocytes 23 and were viable by the acridine orange method. 24 In addition, immunocyto-chemistry (including immunogold staining) and in situ hybridization studies demonstrated that intracellular H pylori can express virulence genes within gastric epithelial cells, as well as immune cells, both in vitro and in vivo.…”
mentioning
confidence: 98%